2021
DOI: 10.1177/01455613211005119
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Office-Based Intralesional Steroid Injections in the Management of Subglottic Stenosis: A Systematic Review

Abstract: Objective: To determine the efficacy of office-based intralesional steroid injections (ILSI) as a management therapy for adult subglottic stenosis (SGS). Data Sources: A systematic review was completed using PubMed and Science Direct for office-based management of SGS due to various etiologies. Review Methods: The primary end point measured was a change in surgery free interval (SFI) between endoscopic procedures due to office-based serial ILSI. The secondary end point was to determine what percentage of patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…Seventy‐nine percentage of the patients did not require additional surgery during the study follow‐up period. This is consistent with the existing pilot literature on SISI with studies demonstrating 70%–82% of patients did not require additional operative dilation 11,14,16 . With a 2‐year minimum follow‐up period and mean follow‐up of 3.41 years, our study demonstrates that SISI can avoid additional operative dilation even over a longer follow‐up period.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Seventy‐nine percentage of the patients did not require additional surgery during the study follow‐up period. This is consistent with the existing pilot literature on SISI with studies demonstrating 70%–82% of patients did not require additional operative dilation 11,14,16 . With a 2‐year minimum follow‐up period and mean follow‐up of 3.41 years, our study demonstrates that SISI can avoid additional operative dilation even over a longer follow‐up period.…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with the existing pilot literature on SISI with studies demonstrating 70%-82% of patients did not require additional operative dilation. 11,14,16 With a 2-year minimum follow-up period and mean follow-up of 3.41 years, our study demonstrates that SISI can avoid additional operative dilation even over a longer follow-up period. In 21 patients with a treatment history prior to receiving SISI, there was a significant improvement in SFI from 13.5 months (2-42 months) prior to SISI to 42 months (10-87 months) after initiating SISI.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The initial SFI for each patient with SGS was determined by the elapsed time between EDs. A systematic review published by Luke et al 22 included three studies (Pan and Rosow, 18 Bertelsen, 32 and Hoffman 33 ) that included the SFI with ED pre‐ and post‐SILSI utilized to calculate the average increase in the SFI.…”
Section: Resultsmentioning
confidence: 99%
“…Although multiple studies have shown the effectiveness of subglottic steroid injections for prolonging the SFI in the case of SGS, 20–23 the cost‐effectiveness of this protocol has yet to be elucidated. Amidst the prominent role of SILSI as an adjuvant treatment to ED for SGS, we investigate whether SILSI is economically justifiable using an analytical observational study of data from the literature and our institution.…”
Section: Introductionmentioning
confidence: 99%